1996
DOI: 10.1097/00005537-199608000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss in Turner Syndrome

Abstract: A retrospective study was undertaken to answer the following questions: Is the sensorineural hearing loss (SNHL) in Turner syndrome progressive? Can the occurrence of hearing loss be explained by the parental origin of the intact X chromosome? Twenty-four individuals recruited through the Turner Syndrome Society completed a questionnaire and submitted sufficient medical records to determine their otologic status. The majority (21/24) have had problematic otitis media (OM), and two thirds (16/24) have SNHL. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 7 publications
4
31
0
Order By: Relevance
“…This study confirms previous reports that the predisposition for CHL develops early in life [5, 27], whilst SNHL is progressive through adult life [1, 28]. Consistent with this, we have shown that the prevalence of CHL remains fairly constant through adult life, whilst there is an increase in the prevalence of SNHL.…”
Section: Discussionsupporting
confidence: 92%
“…This study confirms previous reports that the predisposition for CHL develops early in life [5, 27], whilst SNHL is progressive through adult life [1, 28]. Consistent with this, we have shown that the prevalence of CHL remains fairly constant through adult life, whilst there is an increase in the prevalence of SNHL.…”
Section: Discussionsupporting
confidence: 92%
“…In literature, a history of recurrent middle ear infections is described in 19.6e91% of patients (Anderson et al, 1969;Barrenas et al, 1999;Dhooge et al, 2005;Gawron et al, 2008;Gungor et al, 2000;Hultcrantz et al, 1994;Hultcrantz, 2003;Hultcrantz and Sylven, 1997;Morimoto et al, 2006;Parkin and Walker, 2009;Sculerati et al, 1990Sculerati et al, , 1996Stenberg et al, 1998;Watkin, 1989). Abnormal craniofacial morphology, causing Eustachian tube dysfunction, is suggested as a cause for the recurrent otitis media (Anderson et al, 1969;Gungor et al, 2000;Stenberg et al, 1998).…”
Section: Middle Ear Disease and Otomicroscopic Anomaliesmentioning
confidence: 99%
“…TS literature shows great variability in the reported prevalence of SNHL varying from 9 to 66.7% (Anderson et al, 1969;Barrenas et al, 1999;Beckman et al, 2004;Dhooge et al, 2005;Gawron et al, 2008;King et al, 2007;Morimoto et al, 2006;Sculerati et al, 1990Sculerati et al, , 1996Serra et al, 2003;Watkin, 1989). One study even found a high-frequency SNHL in 98.7% of the patients (mean age 20.8 yr, N ¼ 38) (Gungor et al, 2000).…”
Section: Pure Sensorineural Hearing Loss (Snhl)mentioning
confidence: 99%
“…Excessive otitis media in TS is evident when there is history of myringotomy and tube placement or tympanomastoid surgery, or a medical record documentation of impaired conductive hearing, retraction pocket or cholesteatoma [12]. The conductive losses appear to be secondary to OM and poor Eustachian tube function rather than to any congenital ossicular anomaly.…”
Section: Otitis Media (Om)mentioning
confidence: 99%
“…The result is that the final development of the facial skeleton reaches a level only corresponding to that of an 11-year-old girl, whereas that of the posterior portion of the cranial base is even less advanced, clinicians have noted [10]. This growth dysregulation at the cranial base is in part due to the absence of growth regulating genes for this area such as SHOX [12,13]. As a consequence, not only is the position of the external auditory meats abnormal, giving the appearance of low set ears, but also the relationship of the middle ear to the Eustachian tube is disturbed.…”
Section: Otitis Media (Om)mentioning
confidence: 99%